EFFECT OF MAGNESIUM FLUORIDE IN CHROMIUM-MAGNESIUM CATALYSTS ON THE FLUORINATION REACTION OF 1,1,1-TRIFLUORO-2-CHLOROETHANE - KIM, HG; KIM, HS; LEE, BG; LEE, HJ; KIM, SH (ROYAL SOC CHEMISTRY, 1995)
Magnesium fluoride, mixed with chromium fluoride, enhances the activity, selectivity and lifetime of the chromium catalyst for the vapour-phase fluorination of CF3CH2Cl with anhydrous HF to give CF3CH2F.